Power, readout and service hybrids for the CMS phase-2 upgrade. (1st March 2022) - Zografos, A.; Blanchot, G.; Dominguez, I.M.; Hollos, A.E.; Kovacs, M.I.; Rasevic, N.
Abstract: The CMS tracker phase-2 upgrade silicon modules integrate DC-DC powering stages and an optical transceiver to power and control the front-end hybrids. The strip-strip (2S) module contains a Service Hybrid (2S-SEH) with two-stage DC-DC power conversion, an lpGBT with optical interface (VTRx+), high voltage biasing and temperature sensor ports. The pixel-strip (PS) module utilizes a separate two stage DC-DC converter circuit (PS-POH) and a Readout Hybrid (PS-ROH) containing the communication interface. The design and performance of these three hybrids and their integration in their respective modules are presented.